Plasmid rolling-circle (RC) replication - Khan, Saleem (Henry Stewart Talks, 2008)
Rolling circle replicating (RCR) plasmids, Functional organization of rolling-circle replicating plasmids, Model for plasmid rolling-circle replication, Initiation and termination of replication in plasmids carrying two pT181 dsos, DNA sequence and structure of the pT181 origin, Initiator proteins of RCR plasmids, Comparison of the replication origins of the plasmids of pT181 family, Rep-DNA specificity, Role of individual monomers of the Rep protein, Purification of RepC heterodimers, PcrA helicase, Role of PcrA helicase in plasmid RC replication, Conversion of ss to ds DNA, Single strand origins of replication, Lagging-strand replication